2015
DOI: 10.1021/acs.analchem.5b03709
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of a Monoclonal Antibody–Maytansinoid Immunoconjugate

Abstract: Structural characterization was performed on an antibody-drug conjugate (ADC), composed of an IgG1 monoclonal antibody (mAb), mertansine drug (DM1), and a noncleavable linker. The DM1 molecules were conjugated through nonspecific modification of the mAb at solvent-exposed lysine residues. Due to the nature of the lysine conjugation process, the ADC molecules are heterogeneous, containing a range of species that differ with respect to the number of DM1 per antibody molecule. The DM1 distribution profile of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 41 publications
6
84
2
Order By: Relevance
“…Such conjugation allows for the high selectivity of mAbs to be combined with cytotoxic drugs, achieving discrimination between healthy and diseased tissue in contrast to traditional chemotherapies. While both cysteine and lysine‐targeted chemistries are widely used in ADC generation, the latter typically results in a more heterogeneous drug‐to‐antibody ratio (DAR) distribution, often creating therapeutics with increased structural complexity, owing to the large number of native lysine residues in mAb sequences …”
Section: Introductionmentioning
confidence: 99%
“…Such conjugation allows for the high selectivity of mAbs to be combined with cytotoxic drugs, achieving discrimination between healthy and diseased tissue in contrast to traditional chemotherapies. While both cysteine and lysine‐targeted chemistries are widely used in ADC generation, the latter typically results in a more heterogeneous drug‐to‐antibody ratio (DAR) distribution, often creating therapeutics with increased structural complexity, owing to the large number of native lysine residues in mAb sequences …”
Section: Introductionmentioning
confidence: 99%
“…This fragment ion was generated by cleavage of the ester bond in DM4, as shown in the published results. 18,34 The other fragment ions, such as m/z 262.14 corresponding to the y2 fragment, originated from the peptide. This observation indicated that DM4 was directly conjugated to the side chain of cysteine.…”
Section: The Effect Of Trisulfide Bonds On Conjugation With Dm4mentioning
confidence: 99%
“…In addition to drug-antibody ratio, drug load, free drug, linker, and residual solvent levels are determined. Moreover, container closure, intravenous infusion bag (if applicable), transport, and storage stabilities are rigorously tested (Wakankar et al 2011;Luo et al 2016;Ross and Wolfe 2016).…”
Section: Production and Characterizationmentioning
confidence: 99%